Investigation of crack propagation in the surface white layer of rail steel - A. Yu. Perelygina; V. Yu. Konyukhov; A. E. Balanovskii (Advanced Engineering Research)
Introduction. The paper is devoted to the evaluation of cracking of white layers formed on the surface of the rail while in operation. Cracks are detected in the white layer of rail steel after one thousand test cycles. This is due to tensile and shear stresses on the surface of the wheel-rail contact spot. The paper presents the study results of the morphological characteristics of the white layer on the rail surface.Materials and Methods. The object of study (rail surface after operation) was examined under a microscope. Then, a two-dimensional model of finite elements of the plane deformation was developed to simulate the dynamic characteristics of the white layer cracking. Mathematical models describing crack propagation are proposed. For this, we applied the criterion of the elastic plastic fracture mechanics, the J-integral method. The SYSWELD program performed numerical modeling of the formation of a white layer and the distribution of residual stresses.Results. Optical images of the microstructure of the cross section of a white layer on the rail surface after operation are presented. Two different types of cracks were fixed at the trailing edge of the white layer of the samples studied. The SYSWELD program visualized fragments of simulating the mechanism of the white layer formation with the distribution of residual stresses, compression, and tension. The calculation results show that the values of the J-integral for all three cracks slightly decrease if the crack length reaches 10-50 gm.Discussion and Conclusions. The results obtained are applicable to assess the wear resistance of rail steels and predict the direction of crack growth. Comparisons of J-integral maxima have shown that under identical load conditions, crack no. 1 is likely to grow faster than cracks nos. 2 and 3. With an increase in the length of the crack, the maxima of the J-integral of all three cracks decreased.